Morbidly yours - Fairbanks, Ivy (G.P. Putnam's Sons, 2024)
"An opposites-attract romantic dramedy about a shy, demisexual Irish mortician who must marry by his 35th birthday to keep his beloved family business, and the Texan widow escaping her past who moves in next door"--